Customer Satisfaction Toward Grab Application in Balikpapan - Saputra, Gieska Trisna; Hidayat, Anas (Selekta Manajemen: Jurnal Mahasiswa Bisnis & Manajemen, 2023)
Currently, many people are familiar with e-commerce or online shopping platforms due to their convenience and speed. One of the examples is the Grab application. Behind the rapid development of e-commerce in Indonesia, there are many factors that can contribute to the superiority of one e-commerce platform over another. One important factor is customer satisfaction when they use the services provided by the platform. Customer satisfaction is the primary focus of this research due to the increasingly intense competition in the e-commerce industry. One way to ensure customer satisfaction on e-commerce platforms is by enhancing interface quality, product quality, product variety, and shopping security. When an e-commerce platform provides good service quality and high-quality products, customers will feel satisfied. This satisfaction, in turn, leads to customer loyalty and continued usage of the platform's services. The aim of this study is to examine the influence of interface quality, product quality, product variety, and shopping security on customer satisfaction in the Grab application. The research methodology employed in this study is quantitative. The sample consists of questionnaire responses from 170 users of the Grab application. Data processing in this research utilized AMOS 26 software. The results of the study indicate that interface quality, product quality, and shopping security have a positive and significant partial influence on customer satisfaction.